Forma és tartalom kölcsönhatásai : vita a Vajdaság autonómiájáról - Pap, Tibor (Közép-Európai Közlemények, 2011)
Voivodina came into the focus of Serbian political thought a project that served as territorial framework of ethnic unity. Today, the form of regionalization assumed a hostile content for the protectors of the Serbian unity state. The present paper dicusses the interrelations of form and content in the case of the so-called ’statutum’-debate of the early 2000s, it elaborates on the antiautonomy and regionalisating decentralization arguments and draws a parallel bertewwn the historical contexts of the present and 19th century changes of form and programs of regionalization. To do so within a socio-theoretical framwork, the paper distinguishes between the socio-theoretical analysis of the form of rule and its implications from the subject matter’s aspects of political theory. The ecological implications of the present-day interpretations are examined only inasmuch as they appear in the political discourse. A narrower subjest matter are the politico-theoretical aspects of the „serbian” Voivodina.